Pengaruh kualitas pelayanan penyebrangan terhadap kepuasan pengguna jasa kapal di Pelabuhan Ujung-kamal PT. Asdp Indonesia Ferry (Persero) Cabang Surabaya - Zaiful . Arief (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2017)
This study aims to meet and analyze how much influence the quality of service to the level of satisfaction perceived consumer service users aboard PT.ASDP Indonesia Ferry (persero) Surabaya Branch. Methods used in this study are observation, interviews, questionnaires, sampling methods used Is a Simple Random Sampling of 100 samples. Analytical methods used are multiple linear regression (multi linear regresion). The results showed simultaneously influence the quality of service variables consisting of (Tangible, Reability, Resonsiveness, Assurance, Empaty) and together to variable customer satisfaction, seen from FHitung equal to 19,851 while FTable is 2,31, the number is obtained from table F with value of v1 as 5 as residual and v2 equal to 94 as df (degrees of freedom) with error level 0,05 (5%), considering Fcount> FTable (19,851> 2.31) then simultaneously all independent variables (X) have a significant influence on the dependent variable (Y).